Upstream or swim up processing technique: which one is more effective to select human sperm with high chromatin integrity - Mahnaz Heidari; Niknam Lakpour; Niknam Lakpour; Mahsa Darbandi; Sarai Darban; Saeideh Shani; Leila Goharbakhsh; Ghazaleh Cheshmi; Mohammad Mehdi Akhondi; Mohammad Reza Sadeghi (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Sperm processing methods separate motile sperms with good morphology from dead and abnormal forms of sperms, immature germ cells, and non-sperm cells. Objective: The propose of this study was to compare the efficacy of upstream and swim-up processing techniques to separate sperms with the high quality especially in relation to sperm chromatin integrity. Materials and Methods: This experimental study used semen samples from 60 normozoospermic men. Specimens were divided into equal aliquots for processing by swim up (group A), and upstream (group B) methods and compare with control by raw semen (group C). Sperm concentration, morphology, motility, DNA fragmentation and chromatin maturation were measured in these three groups. Results: The results revealed that sperm concentration in the swim up samples was significantly greater than upstream samples (p≤0.04). as addition, motile sperm recovery including the percentage of progressive motility and a total number of motile sperm was better in the swim-up compared to an upstream method and raw semen (p≤0.001). The cell debris and seminal fluid were equally removed by both methods and the percentage of normal forms was also similar in both procedures (p≥0.4). In addition, sperm DNA fragmentation and chromatin maturation were not significantly different between the three groups (p≥0.1). Conclusion: According to results, apparently the upstream method had no significant efficiency to separate good quality sperms compare to swim up. Therefore, swim up seems to be a simple, inexpensive, reliable and widely available method with an efficient yield to separate motile sperm with good morphology and better chromatin integrity for insemination in the infertility clinics.